Characteristics and outcomes of patients with LAM receiving sirolimus in France based on real-life data - Cottin, Vincent; Cases, Antoine; Bourdin, Virginie; Reynaud-Gaubert, Martine; Hirschi, Sandrine; Kerjouan, Mallorie; Diesler, Rémi; Chardès, Brieux; Fiévez, Stéphane; Assi, Nada; Schmidt, Aurélie; Denis, Hélène; et al. (Frontiers in Medicine, 2025)
LAM is a rare multi-cystic lung disease for which treatment with sirolimus is indicated in cases of moderate or severe lung disease or declining lung function. The aim of this study was to describe patients treated with sirolimus for LAM and their outcomes. This retrospective observational study was based on data from the French national health insurance data system (SNDS). All adult women receiving sirolimus were identified in France between 2014 and 2021. In the absence of a specific LAM code in the system, an algorithm was developed to identify patients treated for possible LAM exclusion of other sirolimus indications (transplantation, graft-versus-host disease), or probable LAM (among possible LAM, patients hospitalized for pneumothorax, pleural drainage, pleurisy, ascites, chronic respiratory failure, lung transplantation, or angiomyolipoma). Over the entire study period, 638 patients were considered as treated with sirolimus for possible LAM, including 208 patients treated for “probable” LAM and 33 patients for TSC-LAM. Median [Q1; Q3] age at index date was 45.0 years [34.0; 58.5] for patients with probable LAM and 40.0 years [28.0; 56.0] for patients with TSC-LAM. Overall, the number of incident patients varied from 28 to 96 each year for possible LAM, from 11 to 33 each year for probable LAM and from 1 to 4 patients each year for TSC-LAM patients. In 2021, the incidence rate of patients treated with sirolimus for probable LAM in France was estimated at 0.9 per 1,000,000 French adult women and the prevalence rate at 6.3 per 1,000,000 French adult women. The 5-year survival after sirolimus initiation was 84% (95% CI: 76%; 90%) for probable LAM patients, and 77% (95% CI: 48%; 91%) for TSC-LAM patients. This study provides an updated epidemiological estimate of LAM patients treated with sirolimus in France between 2014 and 2021. Even though some of the results should be interpreted cautiously in the light of limitations related to the use of claims database, evolution of the disease and missing safety data, the information retrieved in this study is very valuable, as few studies provide real-world information on LAM populations.